Safety and retention of combination triple disease‐modifying anti‐rheumatic drugs in new‐onset rheumatoid arthritis. Issue 12 (December 2015) - Cummins, L.; Katikireddi, V. S.; Shankaranarayana, S.; Su, K. Y. C.; Duggan, E.; Videm, V.; Pahau, H.; Thomas, R.
Abstract: Background: While efficacy of combination treatment with methotrexate (MTX), sulfasalazine (SSZ) and hydroxychloroquine (HCQ) ('triple therapy') has been shown in clinical trials, few studies have examined its longevity in a real‐life setting. Aim: Our aim was to assess the tolerability, longevity and efficacy of a triple disease‐modifying anti‐rheumatic drug (DMARD) regimen initiated in new‐onset rheumatoid arthritis (RA) patients. Methods: Patients who met 1987 American College of Rheumatology criteria for RA with disease duration less than 2 years were offered triple therapy upon diagnosis. Treatment was intensified according to a response‐driven step‐up algorithm, which included progression to leflunomide (LEF) or a biologic agent. Results: Of 181 new‐onset RA patients, 119 commenced triple therapy. Median duration of triple therapy was 39 weeks, and 23.5% remained on it at last follow up, with median follow up 104 weeks. Continuous therapy with any three‐DMARD combination (including LEF) occurred in 32% at last follow up, with median duration of 70 weeks. Cessation of at least one of MTX, SSZ or HCQ occurred because of an adverse event in 38%, remission in 7% and incomplete response in 28% of patients. SSZ accounted for 49% of initial drug withdrawals for an adverse event. Continuation of three‐drug therapy did not significantly influence the proportion of patients achieving remission or low disease activity (LDA). Conclusions: Triple therapy in new‐onset RA was reasonably well tolerated, persisting for median 39 weeks. SSZ intolerance commonly reduces longevity of triple therapy. Treating to the target of remission or LDA is more important than the number of DMARD continued.